The Criteria of Ideal Man as Seen from Female Gaze in Free! - Dita Berlian (Institute of Research and Community Outreach - Petra Christian University, 2019)
Japanese animations (anime) are worldwide known. They are targeted to various kinds of audience. A drama-sport anime entitled Free! is rarely found as the targeted audience is female audience. Because Free! targets female audience, the definition of the ideal men is defined from the point of view of the female audience. Therefore, the gaze which is used to identify the male protagonists is female gaze. By using the theory of male gaze and traditional male sex role themes, I found that there is a combination of masculinity and femininity in the male protagonists in Free!. The combined characteristics are shown in the physical appearance, personality traits, and roles. The appearance of this type of an ideal man leads to a new concept in Japan which is called bishōnen. Keywords: Anime, ideal man, masculinity, femininity, female gaze, bishōnen.